Pembinaan Anak yang Berkonflik dengan Hukum Dari Perspektif Restorative Justice (Studi Perbandingan Antara Indonesia dengan Malaysia) - Fatriansyah Fatriansyah (Legalitas: Jurnal Hukum, 2020)
The purposes of this study are 1) To find and analyze institutions authorized to deal with children in conflict with law in Indonesia and Malaysia, and 2) To find and analyze the process of fostering children in conflict with law in Indonesia and Malaysia. The main problems discussed in this study are 1) Guidance institutions that deal with children in conflict with the law in the future must consider respect for the dignity of children in the form of structural and infrastructure perspectives in coaching institutions in other words a child-friendly coaching institution. Furthermore, to provide protection and the needs of the rights of parents of child development institutions in conflict with the law, it is necessary to prepare the rights for parents or guardians of children who will meet and visit. In addition, from the aesthetic and architectural point of view of building institutions for children in conflict with the law must be child-friendly, so as not to be stigmatized such as prisons or correctional institutions generally for adults. 2) Guidance for children in conflict with the law at this time is only a duty and responsibility of the supervisor in the institution, criminal offender and the community alone, so that restorative justice is not achieved. In the future, the development of children in conflict with law in Indonesia needs to use a restorative justice approach. In each stage of its development, guidance for children in conflict with the law is not only oriented to rehabilitation and resocialization of perpetrators but also recovery of victims and people's lives.